Self-perception of health and physical activity levels among the youth and adults before and amidst the COVID-19 pandemic - Nyawornota, Vida Korleki; Adamba, Clement; Tay, Doris Akosua; Nyanyofio, Oscar C.; Muomah, Rosemary C.; Chukwuorji, JohnBosco C.; Nwonyi, Sampson K.; Malete, Leapetswe; Joachim, Dale; Ocansey, Reginald T. (Frontiers in Public Health, 2024)
Background: There is overwhelming evidence indicating that health status and other mental health correlates (such as depression) may be impacted positively through participation in physical activity (PA), but studies in lower-and middle-income countries and those that involved data at higher physical activity doses were underrepresented. The current study investigated the associations between PA levels and health status and explored the perceptions of health status and PA among youth and adults during the COVID-19 pandemic.The participants were 937 adults 56.5% males, 43.5% females, aged 18-69, mean age=23.6 who completed an online survey as part of the General Health, Speech, and Physical Activity Relationship Assessment Study in Ghana. Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ) short form.The results of this study showed slight variation in PA behaviour among participants before, during and after the COVID-19 pandemic restrictions. The study reported a reduction in PA levels during the pandemic restriction, which is consistent with other studies on the impact of COVID-19 and PA behaviour that also reported a reduction in PA levels. Also, more males were engaging in PA than their female counterparts, which is consistent with studies on COVID-19, health, and PA behaviour. Additionally, participants engaging in PA all the days of the week did not perceive their health status as poor before the COVID-19 restriction.The PA levels of participants decreased during the pandemic period. However, this did not have a significant effect on the self-perceived health status of participants. It is worthy to note that, research evidence exist which strongly supports the view that, individuals who regularly participate in PA were more likely to show improvements in their physical, mental, and emotional health.